2010
DOI: 10.1097/psy.0b013e3181d74c48
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Attenuates Atherosclerosis and Adipose Tissue Inflammation in Socially Isolated ApoE−/− Mice

Abstract: Objective To determine the effect of exogenous oxytocin (OT) administration on inflammation and atherosclerosis in socially isolated apoE−/− mice. Hyperlipidemic animals housed in isolated or stressful social environments display more extensive atherosclerosis than those in an affiliative social environment. The neurohypophyseal peptide OT may be involved in both affiliative social behavior and cardiovascular homeostasis, suggesting a role in mediating the benefits of positive social interactions on atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 36 publications
6
53
0
Order By: Relevance
“…In addition, chronic systemic OT also reduces the expression of pro-inflammatory markers, such as NF-kB, interleukin 1 beta (IL1-β), and interleukin 6 (IL-6) from heart tissue of db/db mice [93] as well as in rats following myocardial infarction [170]. Interestingly, chronic systemic OT also reduces IL-6 secretion from epididymal fat in hyperlipidemic apolipoprotein E (ApoE) deficient mice [187] and C-reactive protein in Watanabe Heritable Hyperlipidemic rabbits [188]. OTR deficient mice also display increased levels of IL1-β, IL-6 and tumor necrosis factor alpha (TNF-α) mRNA expression in the colons following experimental colitis, findings that suggest a possible protective anti-inflammatory effect [160].…”
Section: Does Ot Reduce Inflammation In Animal Models Of Obesity or Hmentioning
confidence: 95%
“…In addition, chronic systemic OT also reduces the expression of pro-inflammatory markers, such as NF-kB, interleukin 1 beta (IL1-β), and interleukin 6 (IL-6) from heart tissue of db/db mice [93] as well as in rats following myocardial infarction [170]. Interestingly, chronic systemic OT also reduces IL-6 secretion from epididymal fat in hyperlipidemic apolipoprotein E (ApoE) deficient mice [187] and C-reactive protein in Watanabe Heritable Hyperlipidemic rabbits [188]. OTR deficient mice also display increased levels of IL1-β, IL-6 and tumor necrosis factor alpha (TNF-α) mRNA expression in the colons following experimental colitis, findings that suggest a possible protective anti-inflammatory effect [160].…”
Section: Does Ot Reduce Inflammation In Animal Models Of Obesity or Hmentioning
confidence: 95%
“…The reduction in cortisol observed within this study is suggestive of this being due to an anxiolytic effect of oxytocin, but anti-inflammatory and antipain effects are also implicated (122). Additionally, oxytocin can reduce atherosclerosis in ApoE -/-mice, again a result of oxytocins antiinflammatory actions (123).…”
Section: Injury and Inflammationmentioning
confidence: 63%
“…Oxytocin receptors are expressed in human endothelial cells and THP1 monocyte and macrophage, oxytocin decreased both superoxide production and release of proinflammatory cytokine from these cells [3]. Oxytocin inhibition of inflammatory cytokines has also been demonstrated in both humans and animals in vivo and ex vivo, which may be mediated by stimulation of the cholinergic antiinflammatory pathways [15,16]. It has been shown that oxytocin abolished the sepsis-induced increase in tumor necrosis factor α, and protected against multiple organ damage [17].…”
Section: Editorialmentioning
confidence: 99%
“…The anti-inflammatory effects of oxytocin are implicated in its regression of atherosclerosis [2,16]. Chronic administration of oxytocin attenuated aortic atherosclerotic lesion development with reduced secretion of the proinflammatory cytokine IL-6 in visceral adipose tissue in social isolated apo-E knockout mice and decreased plasma C-reactive protein level in Watanale Heritble Hyperlipidemic rabbits [12,16]. Clinical and experimental studies have shown that emotion-social stress increases cardiovascular and atherosclerotic diseases [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation